Financial fragility and growth dynamics of Italian business firms - Giulio Bottazzi; Angelo Secchi; Federico Tamagni (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2006)
This work explores a number of properties investigated in the empirical literature on firm size and growth dynamics: (i) the distribution and the autoregressive structure of firm size; (ii) the existence of size-growth scaling relationships; (iii) the distribution and the autoregressive structure of scaling-free growth rates. The major novelty concerns our exploiting of a credit rating index to condition all the analyses upon firms' financial fragility and access to credit. We find that the distributions of both firm size and firm growth rates are fatter tailed among less solvable firms than in the rest of the sample, both at the bottom and at the top extreme of the distributions. As a result, we conclude that not only small and/or slowly growing firms might suffer from difficulties in raising external financing, but also big and fast growing ones might be exposed to financial constraints.
Keywords: L11; C14; D21; G30; 330; firm size; firm growth; financial constraints; Betriebsgröße; Unternehmenswachstum; Betriebliche Kennzahl; Italien